Sinusitis: A Rare Cause for Galactorrhoea - W. O. Bennett; J. R. Kennedy; V. M. Reddy; R. Dyer; S. A. Hickey (Case Reports in Otolaryngology)
A 32-year-old woman presented to the endocrinology clinic with recent onset galactorrhoea. Investigations revealed raised prolactin levels. An MRI scan demonstrated a normal pituitary gland, and an incidental finding of sphenoid sinusitis with expansion of the sphenoid sinus was thought to be due to a mucocele. It is postulated that either the direct local pressure by the mucocele or localised inflammation secondary to sinusitis might cause hyperprolactinaemia. The patient underwent endoscopic surgery to drain the mucocele, after which her galactorrhoea resolved. A review of the literature reveals only one previously documented case of sinusitis causing hyperprolactinaemia and galactorrhoea.